The Effect of Binahong (Anredera Cordifolia) Leaf Extract Intranasal Administration on the Safety of Olfactorius Nerves Wistar Rats - Farhan, Ichsanul; Widuri , Asti; Febriansah , Rifki (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction – Binahong plant (Anredera cordifolia) is reported to contain bioactive compounds that are useful for treating several diseases. One of the effects thatcan be used is anti-inflammatory, so it has potential as an alternative to treat chronic inflammation of the nose, but which has not yet been done researched of safety against the olfactory nerve. Purpose – This study aims to determine the toxic effect of the ethanolic extract of Binahong (Anredera cordifolia) leaves on the safety of the olfactory nerves of Wistar rats. Methodology/Approach – This research is an experimental research using pre and post control group design. The samples used were 30 female Wistar rats aged 3 months which were divided into 6 groups. Group 1 was used as a normal control without treatment. Groups 2, 3, 4, 5 and 6 were treated with a nasal spray of Binahong leaf extract with concentrations of 5%, 10%, 25%, 50% and 75%, respectively. Before and after treatment, the rats were tested for smell by putting them in an empty cage that was fed under the bed and assessing the length of time the rats found food. The data obtained were tested using the t-test (t-test) to see the difference in the mean. Findings – This study showed that there was an effect of Binahong leaf extract (Anredera cordifolia) in reducing the average olfactory time of Wistar rats (241 seconds vs 316 seconds) but it was not statistically significant and no anosmia was found. Originality/ Value/ Implication – The results of this study provide new insights into the use of intranasal Binahong.